Exploring agricultural advice networks, beneficial management practices and water quality on the landscape: A geospatial social-ecological systems analysis. (February 2016) - Baird, Julia; Jollineau, Marilyne; Plummer, Ryan; Valenti, Josh
Highlights: Sources of information and advice for agricultural producers were queried. Producers' land management practices and water quality data were mapped. A 3D geovisualization was created to link social and biophysical data. Regional advisors were most influential in land practice adoption. This technique may contribute to policy development and better practices. Abstract: Agricultural practices have been linked to detrimental effects on ecosystems, with water quality of particular concern. Research has been devoted to understanding uptake of beneficial, or best, management practices (BMPs) in agriculture; however, sources of advice and subsequent effects on the landscape have not been elucidated. This study set out to understand (1) what sources of information agricultural producers rely on when making land-management decisions; (2) the characteristics of their advice networks; and (3) how the advice network linked spatially to water quality on the landscape. A watershed in Alberta was used as a case study and respondents identified that regional advisors were relied upon most often for advice and these advisors had the most influence on the adoption of BMPs. Results indicate that respondents with connections to regional actors implemented more BMPs that those without. Regional government actors had a greater effect than regional non-governmental actors. Local actors played a lesser role in advice networks related to BMP adoption. A 3D geovisualization was used to explore linkages among advisors, BMPs, and water quality. This technique may be useful for other scenarios and can contribute to policy development and enhanced practices.